2017
DOI: 10.1002/stem.2722
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Human Mesenchymal Stem Cells and Platelet-Derived Growth Factor on Human Retinal Ganglion Cells

Abstract: Optic neuropathies such as glaucoma occur when retinal ganglion cells (RGCs) in the eye are injured. Strong evidence suggests mesenchymal stem cells (MSCs) could be a potential therapy to protect RGCs; however, little is known regarding their effect on the human retina. We, therefore, investigated if human MSCs (hMSCs), or platelet‐derived growth factor (PDGF) as produced by hMSC, could delay RGC death in a human retinal explant model of optic nerve injury. Our results showed hMSCs and the secreted growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 50 publications
(76 reference statements)
1
62
0
Order By: Relevance
“…MSCs have shown promising outcomes in preclinical and clinical studies for treating pain and degenerative diseases such as AD, DDD, MS, PD, and RDD and providing immunomodulatory, neuroprotective, and anti‐inflammatory responses in vivo (Beeravolu et al, ; Ding, Kumar, & Mok, ; Gugliandolo, Bramanti, & Mazzon, ; Nasri et al, ; Osborne, Sanderson, & Martin, ; Perez‐Cruet et al, ; Turgeman, ; van Buul et al, ; R. Zhang, Liu, et al, ). Studies have shown that MSCs can be differentiated to NPCs to regenerate the NP in the IVD and to retinal progenitor cells to regenerate the retina within the eye (Beeravolu et al, ; Ding et al, ; Perez‐Cruet et al, ).…”
Section: Opportunitiesmentioning
confidence: 99%
“…MSCs have shown promising outcomes in preclinical and clinical studies for treating pain and degenerative diseases such as AD, DDD, MS, PD, and RDD and providing immunomodulatory, neuroprotective, and anti‐inflammatory responses in vivo (Beeravolu et al, ; Ding, Kumar, & Mok, ; Gugliandolo, Bramanti, & Mazzon, ; Nasri et al, ; Osborne, Sanderson, & Martin, ; Perez‐Cruet et al, ; Turgeman, ; van Buul et al, ; R. Zhang, Liu, et al, ). Studies have shown that MSCs can be differentiated to NPCs to regenerate the NP in the IVD and to retinal progenitor cells to regenerate the retina within the eye (Beeravolu et al, ; Ding et al, ; Perez‐Cruet et al, ).…”
Section: Opportunitiesmentioning
confidence: 99%
“…The neuroprotective effective of different isoforms of PDGF (platelet‐derived growth factor) and hMSCs (human mesenchymal stem cells) were also successfully tested on human retinal explants following positive outcomes in animal models. The results indicated that both stimulate neuroprotective signalling pathways however, hMSCs are more suitable for neuroprotective therapies due to increased RGC survival induced by numerous neurotropic factors secreted by MSCs …”
Section: Successful Applications Of Human Retinal Explants In Culturementioning
confidence: 99%
“…A recent report indicates that photoreceptor precursor cells (PPCs) maturation is accelerated when co‐cultured in the presence of human retinal explants and hESC (human embryonic stem cell)‐derived pigmented epithelium . The hMSCs secrete neurotrophic factors which were shown to have neuroprotective effects on human retinal explants in culture …”
Section: Successful Applications Of Human Retinal Explants In Culturementioning
confidence: 99%
See 1 more Smart Citation
“…While animal models of glaucoma and optic nerve injury indicate that retinal injections of platelet‐derived growth factor‐secreting human mesenchymal stem cells (hMSCs) support RGC survival and protect against vision loss, we understand little about the consequences of hMSC‐therapy in the human retina. A new S tem C ells study from Keith R. Martin (University of Cambridge, United Kingdom) sought to explore this therapeutic option via a novel approach whose findings correlates with the outcomes of in vivo therapies: a human retinal explant model of optic nerve injury . Following the severing of an RGC axon, Osborne et al established that hMSC therapy reduced RGC loss and promoted survival partly via the activation of neuroprotective AKT, ERK, and STAT3 signaling pathways.…”
Section: Featured Articlesmentioning
confidence: 99%